Analysis of the twelve cases of immune-related myocarditis caused by cadonilimab - Chen, Po; Zhao, Zijing; Zheng, Haiying; Li, Jinlan (Frontiers in Oncology, 2025)
ObjectiveThis study aims to analyze the clinical characteristics of immune-related myocarditis caused by cadonilimab, thereby providing a reference for its safe clinical application.MethodsA retrospective analysis was conducted on the medical records of 12 patients diagnosed with immune-related myocarditis caused by cadonilimab at our hospital between January 1st, 2021 and December 31, 2024.ResultsThe incidence of immune-related myocarditis caused by cadonilimab was 2.45% (95%CI:1.30%-4.20%). Among the 12 patients who developed immune-related myocarditis, the majority were female (66.7%) and aged 65 years or younger (83.33%). The median time to onset was 49 days(IQR 27.75, 78), with 10 cases occurring within 90 days following the initial administration. 7 patients were off-label use. Additionally, 7 patients were accompanied by other immune checkpoint inhibitor (ICI)-related adverse events (irAEs), such as hypothyroidism, hepatitis and infusion reactions. 9 patients received glucocorticoid treatment and all of the 12 patients showed improvement and recovery.ConclusionThe clinical use of cadonilimab is complex, necessitating individualized monitoring for immune-related myocarditis based on the patient’s condition. Furthermore, patient education is essential to ensure medication safety.